Informática em saúde e fatores críticos de sucesso: um estudo no INCOR - Carvalho, André de Oliveira (2002)
The evolution of Information Technology (IT) has been a constant in the past decades. However, it is observed that the development level of Informatics in the Health Sector has not happened in the same speed and pace as other sectors that show more dynamics in the adoption of IT resources. This is, in part, due to the particularities of the Health Sector and the lack of a common language with the professionals of the field of Informatics to facilitate the comprehension of the real needs that precede the adequate investments in the field. The methodology of the Critical Success Factors (CSF) is documented here and applied in a case study at the Instituto do Coração (InCor), a Brazilian institution of recognized excellence in services, education and research for health. The CSF methodology has proven a powerful instrument for the identification of the key aspects for the success of individuals and organizations, capable of allowing a clear vision of the areas studied, expressing therefore the needs for Information Systems (lS), pointing priorities for the area of Informatics and enabling the intelligent use of resources. Under the concepts of Business Administration (BA), by characterizing the peculiarities of the Health Sector that refer to IT and IS, it was developed here an extensive theory revision and research applying the methodology of the CSF, in a way to aid the identification and the prioritization of organizational needs, aiming to leveraging for the creative use of Health Informatics.